A biomechanical analysis of ischiofemoral impingement in a cadaver model. Issue 3 (2nd December 2020) - Murata, Yoichi; Fukase, Naomasa; Utsunomiya, Hajime; Brady, Alex W; Rosenberg, Samuel I; Quinn, Patrick; Uchida, Soshi; Martin, Hal David; Philippon, Marc J
Abstract: Ischiofemoral impingement (IFI) occurs due to the diminishing of space between the ischium and lesser trochanter. During a robotic hip study, one hip presented with indications of IFI, an opportunity to explore the pathophysiology and treatment strategies for this unusual condition. This specimen underwent kinematic tests in two states: (i) native lesser trochanter and (ii) resected lesser trochanter. The 'Resected lesser trochanter' state was found to increase the hip range of motion and decrease femoral head translation by eliminating contact between the femur and pelvis. These results suggest that lesser trochanteric resection would provide physical benefit for IFI patients.